Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Dok dan Perkapalan Surabaya Divisi Produksi - Aisya Faradilla Putri; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of work motivation and work discipline on the performance of employees PT. DOK and Shipping. Work motivation is an impulse within an individual that encourages him to do work. Work discipline is the actions taken by individuals in carrying out their work in accordance with applicable rules. Meanwhile performance is the result of employee work. The research sample was determined by Slovin and obtained as many as 82 respondents. Data collection uses questionnaires, and data analysis techniques use multiple linear regression assisted by SPSS. The research results show that work motivation has a positive and significant effect on employee performance partially, work discipline has a positive and significant effect on employee performance partially, work motivation and work discipline have a positive and significant effect on employee performance simultaneously.